Workshop “Mendampingi Belajar” sebagai Upaya Peningkatan Motivasi Belajar Matematika Anak-Anak Kelompok Wanita Tani Berbasis Buku Latihan Bertema Sayuran - Wijayanti, Dyana; Ubaidah, Nila; Asyhari, Asyhari (Universitas Nusantara PGRI Kediri, 2024)
The women farming group/ Kelompok Wanita Tani (KWT) of Manggihan Village, Getasan District, Semarang Regency has carried out organic vegetable cultivation. However, the children of the farmer women's group are not familiar with organic vegetables. In this group there are 22 members and 10 children in grades 1-3 of Elementary School (SD). It was also found that the children's motivation to learn mathematics was low. In addition, KWT's knowledge about the importance of accompanying children while studying is still lacking. From these problems, community service activities focused on workshops 'accompanying children in learning to use the book 'knowing vegetables and counting'. As well as the implementation of child learning assistance by KWT. This activity will be carried out using the offline training method and online implementation. The result of this activity is that children's learning motivation in math lessons increases and the duration of learning assistance by parents (KWT) also increases.